roomXT: Advanced Video Communication for Joint Dining over a Distance - Heidrich, Felix; Kasugai, Kai; Röcker, Carsten; Russell, Peter; Ziefle, Martina (6th International Conference on Pervasive Computing Technologies for Healthcare (PervasiveHealth))
This paper illustrates the development of the roomXT system, a mixed reality communication system for the home domain. RoomXT virtually extends a user's physical environment by providing a “life-like” communication channel for informal and spontaneous interactions. We use a wall-sized display together with head-tracking and 3D rendering to achieve visual contiguity between the real and a virtual environment. As one possible application of this system, we set up a remote dining situation for two users. The dinner table is visually extended into the virtual environment in which a live video stream of the dining partner is shown. Great care was taken in regard to the aesthetic and device-free integration into the living room. First impressions of potential users support the validity of our design decisions.
Keywords: pervasive health; ambient assisted living; video; communication; user-centered design